Governor George Romney and Michigan state representative Nelson Tisdale - Dow Chemical Company (1963)
Photograph of Michigan state representative Nelson G. Tisdale (right) presenting Governor George Romney (left) with a commemorative bottle of Dow aspirin. Tisdale represented Midland, home to the Dow Chemical Company, in the Michigan legislature from 1959 to 1970.
Keywords: Dow Chemical Company; Corporations; Chemical industry; Tisdale, Nelson G.; Romney, George W., 1907-1995; Governors; Public officers